Investigation of sociodemographic variables associated with gambling addiction in adults - İncekara, Harun İsmail and Taş, Besra (Journal of Dependence, 2022)
Objective: The aim of this study was to examine gambling addiction in terms of some demographic variables. Method: The data of the study were collected electronically through Google Form. Survey model, one of the quantitative research methods, was preferred in the study. The study group of the research consists of 400 male individuals living in Osmaniye neighborhood of Bakırköy district of Istanbul province, who play online games of chance from various internet sites and selected by convenient sampling method. Personal Information Form and South Oaks Gambling Addiction Scale prepared by the researcher were used to collect the research data. Results: In the study, a significant difference was found in South Oaks Gambling Screening Test scale scores according to marital status, perception of family relationships, education level of individuals, and perception of themselves as lucky. No significant differences were found in the South Oaks Gambling Screening Test scale scores according to the number of siblings, income levels, number of children, age at the beginning of gambling, education levels of the mothers of the individuals, education levels of the fathers of the individuals, alcohol use status of the individuals, smoking status of the individuals, and psychological social support status of the individuals. Conclusion: It is thought that problematic gambling behavior in individuals may reach dangerous dimensions due to the increasing popularity of gambling in the society and the easy access to gambling with the developing information systems and inadequate control.